2007
DOI: 10.1073/pnas.0702518104
|View full text |Cite
|
Sign up to set email alerts
|

A functional genetic screen identifies retinoic acid signaling as a target of histone deacetylase inhibitors

Abstract: Understanding the pathways that are targeted by cancer drugs is instrumental for their rational use in a clinical setting. Inhibitors of histone deacetylases (HDACI) selectively inhibit proliferation of malignant cells and are used for the treatment of cancer, but their cancer selectivity is understood poorly. We conducted a functional genetic screen to address the mechanism(s) of action of HDACI. We report here that ectopic expression of two genes that act on retinoic acid (RA) signaling can cause resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 35 publications
3
66
0
2
Order By: Relevance
“…First, PRAME is a dominant repressor of RA receptor signaling (Epping et al, 2005), whereas TRAIL is a gene inducible by RA treatment. Second, PRAME is capable of inhibiting the induction of apoptosis by histone deacetylase inhibitors in a concentration-dependent manner (Epping et al, 2007), an event shown to be modulated, at least in leukemia, by induction of TRAIL expression (Insinga et al, 2005;Nebbioso et al, 2005). Indeed, our results clearly showed that in the CML line K562, the inhibition of TRAIL expression is mediated by PRAME and this process relies on EZH2 binding to the TRAIL promoter.…”
Section: Prame-mediated Downregulation Of Trail In CML Dd De Carvalhomentioning
confidence: 54%
“…First, PRAME is a dominant repressor of RA receptor signaling (Epping et al, 2005), whereas TRAIL is a gene inducible by RA treatment. Second, PRAME is capable of inhibiting the induction of apoptosis by histone deacetylase inhibitors in a concentration-dependent manner (Epping et al, 2007), an event shown to be modulated, at least in leukemia, by induction of TRAIL expression (Insinga et al, 2005;Nebbioso et al, 2005). Indeed, our results clearly showed that in the CML line K562, the inhibition of TRAIL expression is mediated by PRAME and this process relies on EZH2 binding to the TRAIL promoter.…”
Section: Prame-mediated Downregulation Of Trail In CML Dd De Carvalhomentioning
confidence: 54%
“…In some cases, this is believed to be a behavioural control mechanism that, for instance, contributes to imprinting action of the environment on the young animal that results in altered behaviour in the mature animal. Epigenetic control via histone acetylation is particularly active in promoting RA signalling, and derepression of RA signalling may be a major rate‐limiting target of histone deacetylase (HDAC) inhibitors (Epping et al, 2007). To explore whether the RA signalling system in the hypothalamus is acted upon by such an epigenetic mechanism, cultured hypothalamic slices were treated with a low concentration of RA (10 nM) which results in weaker induction of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence that the RA signalling pathway is a major target of HDACIs (Epping et al, 2007). Unliganded RARα is known to suppress transcription of RA target genes by recruiting components of the corepressor complex (Hauksdottir et al, 2003), including HDACs, and HDACIs act partly via derepression of RA signalling (Epping et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These initial alterations are most likely to be the drivers. Very powerful genetic systems using RNA interference approaches have also identified previously unsuspected key pathways (18). However, another issue comes to light: what endpoint to consider?…”
Section: Identifying the Relevant Targetsmentioning
confidence: 99%